Providing Advanced Processed Food in an Effort to Reduce Stunting Rates in Sigar Penjalin Village - Padliawan, Muhamad; Sardianto, Sardianto; Nopiana, Rizka; Sonia, Sonia; Wati, Linda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Stunting is a nutritional problem in Indonesia for toddlers and toddlers which is characterized by a height that is shorter than the average age of other children, apart from that, a body weight that is not appropriate for age also affects the child's growth and development, so the child is said to be stunted. There are several problems that cause children to become stunted, not from the age of one year or 2 years, but from within the womb, such as a child in the stomach lacking nutrition and when the child is born, the child does not receive exclusive breast milk from the mother, so the nutrition of the food consumed is not paid attention to by the mother. it will be difficult for the child to develop. Stunting is also a common form of malnutrition in children. How to care is the most important thing to avoid inhibiting growth and development in children. This research aims to determine the number of stunting in toddlers and toddlers aged 20-49 months, and to seek changes to reduce the number of stunted children from the total data of 128 children in Sigar Penjalin village. This research uses qualitative research with a case study approach. Data was obtained by means of in-depth interviews and observations on 40 target children by collecting key information from the B2SA Sigar Penjalin food house, nutrition officers, and posyandu cadres, in areas throughout the Sigar Penjalin village hamlets. The results of the research using in-depth interviews were carried out in collaboration with Rumah Pangan B2SA Sigar Penjalin, following their program, namely providing 4 healthy 5 perfect breakfasts to 40 targets over a period of 3 times a week, 60 times. And our efforts are 6 times providing further preparations (providing vegetables as further preparations at home for children targeted at reducing stunting). Overall, it is hoped that the local government can pay more attention to the community to find out the causes of stunting earlier